Gender peculiarities of psycho-traumatic situations experiencing by the military men in the process of their resocialization during the post-traumatic period - Pryshchepa, M. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
The article is devoted to the analysis of differences in the perception of stressful and psycho-traumatic situations and their influence on personality changes of men and women who took part in the hostilities and who were outside the zone of military conflict during the period of resocialization. The author indicates the features of the socio-political state and those realities that cause a negative impact on the psychological state of soldiers. The reasons for the relevance of the topic of re-socialization of military personnel who have survived traumatic situations are given, and the thesis is expressed on the difference in such a process depending on the gender of the military personnel. The authors' previous experiences on the topics of gender, levels of psychological traumatic situations and their experiences are outlined. Little studied moments have been identified, such as the difference in the perception of stressful and psycho-traumatic situations and their effect on personality changes in men and women who took part in the hostilities and who were outside the zone of military conflict. Recommendations are given on the successful resocialization of servicemen who survived traumatic situations and who were in the combat zone for a certain time. Information is added about the neuropsychological differences between men and women that affect their strategies for experiencing a traumatic situation. The research sample and its features are described, the limitations in the selection and use of research tools are explained. The results are given by quantitative and qualitative methods for which there is a gender difference. Information on the results of the study was summarized, during which the characteristics of the course of emotional and mental disorders in women and men were revealed in the sample, and facts of a decrease in reactive and personal anxiety in military personnel of various genders were revealed.
Keywords: military; psycho-traumatic stress disorder; psycho-traumatic situation; stress tolerance; combat missions